Plasmid DNA for Therapeutic Applications in Cancer - David Hernán Martínez-Puente; José Juan Pérez-Trujillo; Laura Mireya Zavala-Flores; Aracely García-García; Arnulfo Villanueva-Olivo; Humberto Rodríguez-Rocha; Jesús Valdés; Odila Saucedo-Cárdenas; Roberto Montes de Oca-Luna; María de Jesús Loera-Arias (MDPI AG, 2022)
Recently, the interest in using nucleic acids for therapeutic applications has been increasing. DNA molecules can be manipulated to express a gene of interest for gene therapy applications or vaccine development. Plasmid DNA can be developed to treat different diseases, such as infections and cancer. In most cancers, the immune system is limited or suppressed, allowing cancer cells to grow. DNA vaccination has demonstrated its capacity to stimulate the immune system to fight against cancer cells. Furthermore, plasmids for cancer gene therapy can direct the expression of proteins with different functions, such as enzymes, toxins, and cytotoxic or proapoptotic proteins, to directly kill cancer cells. The progress and promising results reported in animal models in recent years have led to interesting clinical results. These DNA strategies are expected to be approved for cancer treatment in the near future. This review discusses the main strategies, challenges, and future perspectives of using plasmid DNA for cancer treatment.